Work stress management model through digital humor - MUNIR, MISNAL; AMALIYAH, AMALIYAH; PANDIN, MOSES GLORINO RUMAMBO (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This study aims to manage stress through digital humor in an effort to improve the quality of work life. The research method uses a quantitative approach. Respondents are members of the WhatsApp Indonesian Lecturer Community group with a total of 120 people. The work stress that a teacher feels is quite high, that is, when a teacher is more intense in the use of humor in digital media, in the middle of his work schedule, the work stress that he feels will actually increase, then the perceived quality of work life will actually decrease. But in this study it was not possible to verify that the work stress variable is significantly related to the influence of digital humor on the quality of work life. RESUMEN Este estudio tiene como objetivo gestionar el estrés a través del humor digital en un esfuerzo por mejorar la calidad de vida laboral. El método de investigación utiliza un enfoque cuantitativo. Los encuestados son miembros del grupo WhatsApp Indonesian Lecturer Community con un total de 120 personas. El estrés laboral que siente un profesor es bastante alto, es decir, un profesor cuando es más intenso en la utilización del humor en los medios digitales, en medio de su horario de trabajo, el estrés laboral que se siente en realidad aumentará, entonces la calidad de vida laboral percibida realmente disminuirá. Pero en este estudio no se pudo comprobar que la variable de estrés laboral este relacionada significativamente con la influencia del humor digital en la calidad de vida laboral.